Role of Rostral Ventrolateral Medullary ERK/JNK/p38 MAPK Signaling in the Pressor Effects of Ethanol and Its Oxidative Product Acetaldehyde. (26th July 2013) - El‐Mas, Mahmoud M.; Fan, Ming; Abdel‐Rahman, Abdel A.
Abstract : Background: We tested the hypothesis that alterations of the phosphorylation/dephosphorylation profile of mitogen‐activated protein kinases (MAPKs) in the rostral ventrolateral medulla (RVLM) underlie the pressor response elicited by ethanol (EtOH) microinjection into the RVLM of spontaneously hypertensive rats (SHRs). The studies were extended to determine whether acetaldehyde (ACA), the primary oxidative product of EtOH, replicates the molecular effects of EtOH within the RVLM and the consequent pressor response. Methods: Effects of EtOH or ACA on blood pressure (BP) were evaluated in the absence or presence of selective JNK (SP600125), ERK (PD98059), p38 (SB203580), or ser/thr phosphatases (okadaic acid [OKA]) inhibitor. Results: Intra‐RVLM EtOH (10 μg/rat) or ACA (2 μg/rat) caused a similar ERK2‐dependent pressor response because EtOH or ACA‐evoked increases in BP and in RVLM p‐ERK2 level were abolished after pharmacologic inhibition of ERK phosphorylation. SP600125 abrogated the pressor action of EtOH, but not ACA, thus implicating JNK in EtOH action on BP. Despite EtOH enhancement of p38 phosphorylation, pharmacological studies argued against a causal role for this kinase in EtOH‐evoked pressor response. RVLM phosphatase catalytic activity was not influenced by EtOH or ACA. Interestingly, pharmacologic phosphatase inhibition (OKA), which increased RVLM p‐ERK2 and BP, abrogated the pressor effect of subsequently administered EtOH or ACA. Conclusions: Enhancement of RVLM ERK2 phosphorylation constitutes a major molecular mechanism for the pressor response elicited by intra‐RVLM EtOH or its metabolite, ACA, in conscious SHRs. Further, RVLM kinases dephosphorylation does not contribute to intra‐RVLM EtOH‐ or ACA‐evoked pressor response.